2021
DOI: 10.1021/acs.orglett.1c01750
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Cyclopropenation of Alkynes with Diazirines as Carbene Precursors in Continuous Flow

Abstract: An efficient synthesis of 3-trifluoromethyl-3-aryl-cyclopropenes via the cyclopropenation reaction of alkynes with photolytically generated carbenes from diazirine compounds is described. This reaction is performed in continuous flow using readily available LEDs under mild reaction conditions. This new and efficient method describes the synthesis of 25 examples of 3-trifluoromethyl-3-arylcyclopropenes with yields up to 97%, achieved in continuous flow with a 5 min residence time. Control experiments highlighte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Thus, diazirines are, by far, better substrates for accessing diaryl trifluoromethyl cyclopropenes by LED irradiation. Noteworthy, isomerization of the diazirine into the diazoalkane takes place to some extent, as demonstrated by in situ IR studies …”
Section: Cycloadditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, diazirines are, by far, better substrates for accessing diaryl trifluoromethyl cyclopropenes by LED irradiation. Noteworthy, isomerization of the diazirine into the diazoalkane takes place to some extent, as demonstrated by in situ IR studies …”
Section: Cycloadditionsmentioning
confidence: 99%
“…Although aryl trifluoromethyl diazo and diazirine compounds have been less extensively studied in the past than diazoalkanes and diazirines substituted with an aryl and an ester, ,, the number of publications describing challenging synthetic methods using this class of reactant is now rapidly growing. Aryl trifluoromethyl diazo and diazirine compounds have been used in various types of reactions, ranging from cycloaddition to insertion and coupling reactions.…”
Section: Introductionmentioning
confidence: 99%
“… 53 In 2021, the Ollevier group reported the use of diazirines to access trifluoromethyl cyclopropenes. 54 A range of light sources and diazirine precursors were investigated for the cyclopropenation of diphenylactylene. As expected, the wavelength of the light source was dependent on the structure and absorbance profile of the starting diazirine, with some diazirines being active at 420 nm and others requiring more energetic light (405 or 380 nm).…”
Section: Use Of Carbenes In Continuous Flowmentioning
confidence: 99%
“…Similar reactivity can also be achieved via the photochemical decomposition of diazirines . In 2021, the Ollevier group reported the use of diazirines to access trifluoromethyl cyclopropenes . A range of light sources and diazirine precursors were investigated for the cyclopropenation of diphenylactylene.…”
Section: Use Of Carbenes In Continuous Flowmentioning
confidence: 99%
“…10−19 Curiously, while diazo compounds have been used in synthetic chemistry, their structural isomers (diazirines) have been reserved to other applications as photolabeling reagents of proteins 20,21 or polymer crosslinking. 10 The trend with diazirines has changed only recently. 10,19 With regard to the spin and electronic states of carbene photolytically formed, Prof. Platz et al have recently published an article 22 within a special issue in honor of Prof. Carpenter in which it is found that the photolysis of 1-phenyl-1-diazopropane (PDP) depends on the irradiating wavelength.…”
Section: ■ Introductionmentioning
confidence: 99%